Spatial organization of Dps and DNA–Dps complexes. Issue 10 (14th May 2021) - Dubrovin, Evgeniy V.; Dadinova, Liubov A.; Petoukhov, Maxim V.; Soshinskaya, Ekaterina Yu.; Mozhaev, Andrey A.; Klinov, Dmitry V.; Schäffer, Tilman E.; Shtykova, Eleonora V.; Batishchev, Oleg V.
Graphical abstract: Highlights: Dps protects bacterial genome from harmful effects by co-crystallization with DNA. DNA does not wrap Dps molecules in DNA–Dps complexes in vitro. Dps molecule contacts with a DNA segment of ~6 nm length. DNA is condensed by small quasi-crystal Dps arrangements in vitro. DNA may arrange along the rows of ordered Dps molecules in DNA–Dps co-crystals. Abstract: DNA co-crystallization with Dps family proteins is a fundamental mechanism, which preserves DNA in bacteria from harsh conditions. Though many aspects of this phenomenon are well characterized, the spatial organization of DNA in DNA–Dps co-crystals is not completely understood, and existing models need further clarification. To advance in this problem we have utilized atomic force microscopy (AFM) as the main structural tool, and small-angle X-scattering (SAXS) to characterize Dps as a key component of the DNA-protein complex. SAXS analysis in the presence of EDTA indicates a significantly larger radius of gyration for Dps than would be expected for the core of the dodecamer, consistent with the N-terminal regions extending out into solution and being accessible for interaction with DNA. In AFM experiments, both Dps protein molecules and DNA–Dps complexes adsorbed on mica or highly oriented pyrolytic graphite (HOPG) surfaces form densely packed hexagonal structures with a characteristic size of about 9 nm. To shed light on the peculiarities of DNA interaction with Dps molecules, we have characterized individual DNA–Dps complexes. Contour length evaluation has confirmed the non-specific character of Dps binding with DNA and revealed that DNA does not wrap Dps molecules in DNA–Dps complexes. Angle analysis has demonstrated that in DNA–Dps complexes a Dps molecule contacts with a DNA segment of ~6 nm in length. Consideration of DNA condensation upon complex formation with small Dps quasi-crystals indicates that DNA may be arranged along the rows of ordered protein molecules on a Dps sheet.